1. Determining the value of x and y:
Given equation(s):
To determine the point of intersection given by the two equations, it is required to know the x-value and the y-value of both equations. We can solve for the x and y variables through two methods.
Method-1: Substitution method
Given value of the y-variable: 3x - 1
Substitute the given value of the y-variable into the second equation to determine the value of the x-variable.
![\implies 3x + y = -7](https://img.qammunity.org/2023/formulas/mathematics/college/8s2nzjl8p2utvtji7u68mg0v2e5v8ffbqt.png)
![\implies3x + (3x - 1) = -7](https://img.qammunity.org/2023/formulas/mathematics/college/lw8jrckzhumsdwwr79r6l69skcltwf8w8w.png)
![\implies3x + 3x - 1 = -7](https://img.qammunity.org/2023/formulas/mathematics/college/60daa4ssoo9ha1yymzy6v1jc9fezkurpft.png)
Combine like terms as needed;
![\implies 3x + 3x - 1 = -7](https://img.qammunity.org/2023/formulas/mathematics/college/mhvvauy9l7xp4kq0h8eoxtry6jhnx2569l.png)
![\implies 6x - 1 = -7](https://img.qammunity.org/2023/formulas/mathematics/college/nisadjxp85tob5txj1wryfdgkc41x4aldt.png)
Add 1 to both sides of the equation;
![\implies 6x - 1 + 1 = -7 + 1](https://img.qammunity.org/2023/formulas/mathematics/college/7ay4ojbp3h3m44gxq7mc7r69ac4ecr19q4.png)
![\implies 6x = -6](https://img.qammunity.org/2023/formulas/mathematics/college/tu8vb1knaouukyz1ninefna7ipfixxs162.png)
Divide 6 to both sides of the equation;
![\implies (6x)/(6) = (-6)/(6)](https://img.qammunity.org/2023/formulas/mathematics/college/tq2plew52lm9ccz8wyf5kali2nrkwa7duv.png)
![\implies x = -1](https://img.qammunity.org/2023/formulas/mathematics/college/7nafco7xpmt7qzvu2a0uc938llv9axgtbt.png)
Now, substitute the value of the x-variable into the expression that is equivalent to the y-variable.
![\implies y = 3(-1) - 1](https://img.qammunity.org/2023/formulas/mathematics/college/e1py6s9jgkyxk9w1anc7ygozo5v6uwqbeu.png)
![\ \ = -3 - 1](https://img.qammunity.org/2023/formulas/mathematics/college/g1x1xav0nxdvbecfzim7t4ieic1khy8fvj.png)
![= -4](https://img.qammunity.org/2023/formulas/mathematics/college/5zzb0ym97yye4y8flxibeoya05xra9c5o1.png)
Therefore, the value(s) of the x-variable and the y-variable are;
![\boxed{y = -4}](https://img.qammunity.org/2023/formulas/mathematics/college/6ammlcdp5at09yln9hh4apdnfc9lpf2xoy.png)
Method 2: System of equations
Convert the equations into slope intercept form;
![\implies\left \{ {{y = 3x - 1} \atop {3x + y = -7}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/56cp5hlunqojrbevd7wtvb2woz8zchux0o.png)
![\implies \left \{ {{y = 3x - 1} \atop {y = -3x - 7}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/psmy917u65ke506nhrp8153sa9uw8c39wz.png)
Clearly, we can see that "y" is isolated in both equations. Therefore, we can subtract the second equation from the first equation.
![\implies \left \{ {{y = 3x - 1 } \atop {- (y = -3x - 7)}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/nfkgrdi64w7wmvwxpvtj4w4fe4ayj1t6l6.png)
![\implies \left \{ {{y = 3x - 1} \atop {-y = 3x + 7}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/h4xqr4l7aogdm90oczsszr2fidhf2qe7c6.png)
Now, we can cancel the "y-variable" as y - y is 0 and combine the equations into one equation by adding 3x to 3x and 7 to -1.
![\implies\left \{ {{y = 3x - 1} \atop {-y = 3x + 7}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/nz4fb15c3tu4cywkjmjhuj0xiwxmkiz58v.png)
![\implies 0 = (6x) + (6)](https://img.qammunity.org/2023/formulas/mathematics/college/ymmhads2igjvbnz7juwkwr44gc83nr8q19.png)
![\implies0 = 6x + 6](https://img.qammunity.org/2023/formulas/mathematics/college/w8e1ox9ryitu5uz4hzqrhrcr1j42jj2rr3.png)
This problem is now an algebraic problem. Isolate "x" to determine its value.
![\implies 0 - 6 = 6x + 6 - 6](https://img.qammunity.org/2023/formulas/mathematics/college/waqmbzct63cq1kvn1jst2f9oh9gx4rpedy.png)
![\implies -6 = 6x](https://img.qammunity.org/2023/formulas/mathematics/college/octlzofg0h2igvxiybnaoygxj7esfx8k7g.png)
![\implies -1 = x](https://img.qammunity.org/2023/formulas/mathematics/college/emrs0fxim0o0nvqfzwsv4wp8eeoqrgkgjk.png)
Like done in method 1, substitute the value of x into the first equation to determine the value of y.
![\implies y = 3(-1) - 1](https://img.qammunity.org/2023/formulas/mathematics/college/e1py6s9jgkyxk9w1anc7ygozo5v6uwqbeu.png)
![\implies y = -3 - 1](https://img.qammunity.org/2023/formulas/mathematics/college/d8ytxk08xad2qukr10lg0t5lg33wouaq56.png)
![\implies y = -4](https://img.qammunity.org/2023/formulas/mathematics/college/yzutx1kjwlasx4pkqp2t8s59542swaf3y8.png)
Therefore, the value(s) of the x-variable and the y-variable are;
![\boxed{y = -4}](https://img.qammunity.org/2023/formulas/mathematics/college/6ammlcdp5at09yln9hh4apdnfc9lpf2xoy.png)
2. Determining the intersection point;
The point on a coordinate plane is expressed as (x, y). Simply substitute the values of x and y to determine the intersection point given by the equations.
⇒ (x, y) ⇒ (-1, -4)
Therefore, the point of intersection is (-1, -4).
Graph: